Modeling Dexterity Development in 2nd-4th-grade Boys by Means of Active Games - C. Марченко (OVS LLC, 2017)
The objective is to optimize the mode of using game for dexterity development in the 2nd-4th-grade boys. Materials & methods: to conduct the experiment, there were eight test groups (n=48) formed in each class. The total number of such test groups was 24. The research relied on the following methods: theoretical analysis and collation of scientific and methodological literature; pedagogical testing; methods of mathematical experiment planning (complete factorial experiment 23); modeling method. Results: the research has determined that to develop dexterity, the 2nd-4th-grade boys need to participate in up to five games. The number of repetitions for the 2nd-3rd-graders is two, and for the 4th-graders - three, with 30-40-second rest intervals. The 2nd-4th-grade boys showed effective development during 40 classes, and the 3rd-grade boys - during 20 classes. After that, we recommend to use other means. The game duration varies from one to two minutes. Conclusions: the analysis of the scientific and methodological literature has revealed that the level of motor readiness, dexterity being one of its main components, largely determines the state of children's physical and mental health. The research has found that the natural development of coordination abilities in boys aged between 7 and 10 is 22.5-80.0% (56.2% on average). Game actions play a particular role in dexterity development in junior schoolers. The 23 complete factorial experiment made it possible to study the multi-factorial structure of game load for the 2nd-4th-graders; to specify the relations between factors for their use during dexterity development in the 2nd-4th-grade boys in physical education classes. They can serve as an objective tool for the educational process optimization. The given regression equations are models that can be used to determine the optimal game means ratio in the academic process of the 2nd-4th-graders.